Identification of Potential Anti-Neuroinflammatory Inhibitors from Antarctic Fungal Strain Aspergillus sp. SF-7402 via Regulating the NF-κB Signaling Pathway in Microglia - Thao Quyen Cao; Zhiming Liu; Linsha Dong; Hwan Lee; Wonmin Ko; Le Ba Vinh; Nguyen Quoc Tuan; Youn-Chul Kim; Jae Hak Sohn; Joung Han Yim; Dong-Sung Lee; Hyuncheol Oh (Molecules, 2022)
Microglia play a significant role in immune defense and tissue repair in the central nervous system (CNS). Microglial activation and the resulting neuroinflammation play a key role in the pathogenesis of neurodegenerative disorders. Recently, inflammation reduction strategies in neurodegenerative diseases have attracted increasing attention. Herein, we discovered and evaluated the anti-neuroinflammatory potential of compounds from the Antarctic fungi strain Aspergillus sp. SF-7402 in lipopolysaccharide (LPS)-stimulated BV2 cells. Four metabolites were isolated from the fungi through chemical investigations, namely, 5-methoxysterigmatocystin (1), sterigmatocystin (2), aversin (3), and 6,8-O-dimethylversicolorin A (4). Their chemical structures were elucidated by extensive spectroscopic analysis and HR-ESI-MS, as well as by comparison with those reported in literature. Anti-neuroinflammatory effects of the isolated metabolites were evaluated by measuring the production of nitric oxide (NO), tumor necrosis factor (TNF)-α, and interleukin (IL)-6 in LPS-activated microglia at non-cytotoxic concentrations. Sterigmatocystins (1 and 2) displayed significant effects on NO production and mild effects on TNF-α and IL-6 expression inhibition. The molecular mechanisms underlying this activity were investigated using Western blot analysis. Sterigmatocystin treatment inhibited NO production via downregulation of inducible nitric oxide synthase (iNOS) expression in LPS-stimulated BV2 cells. Additionally, sterigmatocystins reduced nuclear translocation of NF-κB. These results suggest that sterigmatocystins present in the fungal strain Aspergillus sp. are promising candidates for the treatment of neuroinflammatory diseases.